Reduced Graphene Oxide-Based Impedimetric Immunosensor for Detection of Enterotoxin A in Milk Samples - Rocha, Giovanna S. [UNESP]; Silva, Martin K. L. [UNESP]; Cesarino, Ivana [UNESP] (My University, 2020)
A simple, cheap, and less aggressive immobilization procedure for biomolecules using reduced graphene oxide (rGO) was employed to prepare an impedimetric immunosensor for detection of staphylococcal enterotoxin A (SEA) from Staphylococcus aureus in milk samples. The scanning electron microscopy, cyclic voltammetry, and electrochemical impedance spectroscopy (EIS) were used to monitor the single steps of the electrode assembly process. The glassy carbon (GC)/rGO platform detected the antigen-antibody binding procedures of SEA with concentrations of 0.5 to 3.5 mg L-1 via impedance changes in a low frequency range. The impedimetric immunosensor was successfully applied for the determination of SEA in milk samples.
Keywords: EnterotoxinA; Impedimetric immunosensor; Reduced graphene oxide; Staphylococcus aureus